2021
DOI: 10.1021/acs.jpcc.1c06676
|View full text |Cite
|
Sign up to set email alerts
|

Optical Property of Inorganic Halide Perovskite Hexagonal Nanocrystals

Abstract: Inorganic halide perovskite nanocrystals (NCs) exhibit many excellent optical and semiconductor properties. Herein, CsPbBr3 hexagonal NCs (HNCs) have been synthesized, and their photophysical behavior has been investigated in detail. The CsPbBr3 cubic NCs (CNCs) act as references. The CsPbBr3 HNCs exhibit apparent linear and two-photon fluorescence properties, and their two-photon absorption cross section is 4668.7 GM. In addition, the energy band, radiative channel, and carrier recombination of CsPbBr3 HNCs h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…This specificity can form hexagonal PeNCs, which are different from the typical square crystals. It was found that the PL behavior of hexagonal PeNCs is usually better than that of typical square-shaped PeNCs [26] . These characteristics can be analyzed indirectly by density functional theory (DFT) calculation etc.…”
Section: Resultsmentioning
confidence: 99%
“…This specificity can form hexagonal PeNCs, which are different from the typical square crystals. It was found that the PL behavior of hexagonal PeNCs is usually better than that of typical square-shaped PeNCs [26] . These characteristics can be analyzed indirectly by density functional theory (DFT) calculation etc.…”
Section: Resultsmentioning
confidence: 99%
“…While most perovskite nanocrystals (NCs) exhibit a cubic morphology, recent studies have demonstrated the ability to fine-tune the intrinsic optical and catalytic properties of lead bromide perovskite NCs by precisely controlling facet growth and shape. 11 In this vein, synthetic efforts to modulate the shape of CsPbBr 3 NCs have been extensively carried out, either by the addition of other metals like Cd and Mn, 12 by lowering the injection temperature, by post synthetic modifications of Cs 4 PbBr 6 NCs, 13 or by changing the commonly used long-chain ligands to short-chain amines. 14 However, few reports focus on studying the effect of other surfactants than OAm/OA as capping ligands in the facet growth of CsPbBr 3 NCs.…”
Section: Communicationmentioning
confidence: 99%
“…(H, I) pressure dependence of monomolecular recombination rate (H) and bimolecular recombination rate (I) of CsPbBr 3 hexagonal NCs and CNCs. Reproduced with permission from ref . Copyright 2021 American Chemical Society.…”
Section: Pressure-induced Structural and Property Changes In Perovski...mentioning
confidence: 99%